Distribusi dan Karakteristik Sampah Laut di Ekosistem Mangrove Perancak, Kabupaten Jembrana, Bali - Tarigan, Afri Pradinanta; Hendrawan, I Gede; Wiyanto, Dwi Budi (Journal of Marine Research and Technology, 2025)
Marine debris is a major source of pollution in mangrove ecosystems. Several studies have suggested that marine debris has a negative impact on biodiversity in mangrove ecosystems. The Perancak mangrove ecosystem in Jembrana Regency, Bali Province, is vulnerable to marine debris pollution. This is because the Perancak mangrove ecosystem is where six rivers flow: the Loloan River, Budeng River, Tibukleneng River, Samblong River, Air Kuning River, and Awen River. The river flows through the urban area of Jembrana Regency before emptying into the Perancak mangrove ecosystem, so there is a high possibility of waste entering the river and emptying into the Perancak mangrove ecosystem. This study aimed to determine the characteristics and distribution of marine debris in the Perancak mangrove ecosystem. Marine debris data collection was conducted by adapting the method developed by the Commonwealth Scientific and Industrial Research Organization (CSIRO). Marine debris was distributed almost throughout the Perancak mangrove ecosystem with a concentration range between 0.22-2.22 items/m² and an average of 0.8 items/m². As much as 89% of the debris was plastic, which was dominated by three main classes, namely soft plastic (72.68%), hard plastic (11.57%), and foam (3.20%). 78.25% of the debris in the Perancak mangrove ecosystem was whole, and the rest were fragments. The dominant size of marine debris in the Perancak mangrove ecosystem is 8-16 cm (33.08%). Marine debris is the residual waste of human activities intentionally dumped or carried by the river flow that empties into the Perancak mangrove ecosystem.